Estimated pulse wave velocity and the risk of acute kidney injury in patients undergoing coronary revascularization: a retrospective cohort study from MIMIC-IV - Xinping Yang; Lizi Zhang; Hao Wei; Fan Zhang; Han Yang; Jiahua Shi (Renal Failure, 2025)
Acute kidney injury (AKI) commonly complicates coronary revascularization, worsening outcomes. Estimated pulse wave velocity (ePWV), a simple arterial stiffness marker, independently predicts cardiovascular risk. This study aimed to evaluate the association between ePWV and AKI in patients undergoing coronary revascularization. Based on the Medical Information Mart for Intensive Care (MIMIC)-IV database, this retrospective cohort study obtained the data of patients who underwent coronary revascularization, including percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG). The ePWV was calculated based on the patients’ age and blood pressure. Univariable and multivariable logistics regression were utilized to evaluate the association between ePWV and AKI in this population, with odds ratio (ORs) and 95% confidence intervals (CIs). Stratified analyses based on age, gender, surgery types, complications were further conducted to verify this association. This study ultimately included 2,842 eligible patients who underwent coronary revascularization. Among them, 1,174 (41.31%) occurred AKI. We observed high ePWV is associated with high risk of AKI in patients received coronary revascularization (OR = 1.36, 95%CI: 1.10-1.69). Similar results were also observed in patients who underwent CABG (OR = 1.08, 95%CI: 0.96-1.21), without the history of acute myocardial infarction (OR = 1.39, 95%CI: 1.06-1.82), or atrial fibrillation (OR = 1.36, 95%CI: 1.07-1.73), or with the history of hypertension (OR = 1.48, 95%CI: 1.12-1.95) or had higher estimated glomerular filtration rate (eGFR) level (OR = 1.45, 95%CI: 1.16-1.81). The results suggested high ePWV is associated with the high risk of AKI among patients underwent coronary revascularization. The ePWV is a simple and noninvasive indicator that could be used for risk stratification of AKI after coronary revascularization.